EPR studies of the Mo-enzyme aldehyde oxidoreductase from Desulfovibrio gigas: An application of the Bloch–Wangsness–Redfield theory to a system containing weakly-coupled paramagnetic redox centers with different relaxation rates - González, Pablo J. (2009)
Electron transfer proteins and redox enzymes containing paramagnetic redox centers with different relaxation rates are widespread in nature. Despite both the long distances and chemical paths connecting these centers, they can present weak magnetic couplings produced by spin-spin interactions such as dipolar and isotropic exchange. We present here a theoretical model based on the Bloch-Wangsness-Redfield theory to analyze the dependence with temperature of EPR spectra of interacting pairs of spin 1/2 centers having different relaxation rates, as is the case of the molybdenum-containing enzyme aldehyde oxidoreductase from Desulfovibrio gigas. We analyze the changes of the EPR spectra of the slow relaxing center (Mo(V)) induced by the faster relaxing center (FeS center). At high temperatures, when the relaxation time T(1) of the fast relaxing center is very short, the magnetic coupling between centers is averaged to zero. Conversely, at low temperatures when T(1) is longer, no modulation of the coupling between metal centers can be detected.